SUCCESION PLANNING IN A FAMILY BUSINESS; CASE STUDY OF PT. XYZ. - Rohmat, Eep Saipul; Ande, Diin Fitri (IKRA-ITH EKONOMIKA, 2018)
ABSTRACTCurrently the majority of private companies in Indonesia is controlled by the family. However,Succession is the most difficult challenge in family business. A bit of a family company that isable to survive up to the fourth generation. Statistics show that the success of leadershipsuccession from first generation to second generation just only around 30%, while the rest (70%)experienced a failure, while the success rate of the second generation to third generation droppedsignificantly to only 7% only (Mangalandum, 2013 ). Thus, the problem of succession becomes anissue that must be reviewed in greater depth in relation to the existence of a family company.This paper analyses the formulation of succession in the family company of PT. XYZ, aconstruction company. From 2005 until 2016, the company management has been doing thesuccession program into the hands of the second generation. Formulation succession in in PT.XYZ is done by analyzing the succession process and the challenges faced by company usingsuccession planning roadmap developed by Clifford and succession planning in the context ofhuman capital planning by Booz Allen. Through an understanding going on in the elements of thesuccession process, the main issues that could potentially be an obstacle in the process ofsuccession can be known.